Regional pattern of child undernutrition, calorie consumption, non-food expenditure and wealth in India - Junaid Khan; Sanjay K. Mohanty (Elsevier, 2022)
Background/objective: Although, proximate and contextual determinants of malnutrition have been studied previously, there are a limited number of studies on association of calories consumption, economic wellbeing of household and measures of child undernutrition. In this context, this study examined the regional level variation in child undernutrition in terms of calories consumption, monthly per capita non-food expenditure (MPCNFE) and mean wealth score. Methods: This study is based upon NFHS, 2015-16 and NSS, 2011-12 datasets. Compiling the necessary information at the regional level, this study employed bi-variate cross-tabulation, correlation analysis and multivariate OLS regression analysis. Results: Regions where calories intake is more than 2200 Kcal, the prevalence of stunting (31%), underweight (27%) and wasting (19%) are comparatively low. A low MPCNFE (<1000 R/-) shows higher prevalence of stunting (39%), underweight (33%) and wasting (21%) across regions. Similarly, a low wealth score also shows higher prevalence of undernutrition across regions of India. OLS estimation shows that calories intake significantly predicts all the three measures of undernutrition at the regional level explaining 45% of the regional variation in stunting, 52% in the prevalence of underweight and 38% in wasting. The MPCNFE measure significantly predicts the regional level variation in stunting (Adjusted R2 = 0.54) and underweight (Adjusted R2 = 0.35) but not wasting. The wealth framework is observed to be weak and shows statistically significant association with stunting only and the explained variation is also found low (Adjusted R2 = 0.16). Conclusion: This study provides compelling evidence on the regional variation in child undernutrition parameters in terms of calories intake, MPCNFE and wealth score.